2014
DOI: 10.15835/buasvmcn-agr:9730
|View full text |Cite
|
Sign up to set email alerts
|

Feed forms of different particle sizes: growth response, carcass yield and intestinal villus morphology of growing rabbits

Abstract: Several studies revealed inconsistencies in recommended feed particle size for optimal growth and productive performance of rabbits. Information on the interaction effect of feed form and feed particle size on rabbit’s growth performance and gut morphology is thereby a growing concern. Hence, the growth response, carcass yield and intestinal villus morphology of thirty-six growing male rabbits of mixed breeds (Chinchilla × New Zealand White) weighing between 550-600g were determined using two feed forms (FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…influenced by feed form. The result of feed form on cost benefits in this study was in agreement with the report of Sogunle et al 13 which states that feed form and particle size had no significant (p>0.05) effects on the parameters measured. The cost of pelletizating will be higher than the mash feed because of the cost of pelletizing.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…influenced by feed form. The result of feed form on cost benefits in this study was in agreement with the report of Sogunle et al 13 which states that feed form and particle size had no significant (p>0.05) effects on the parameters measured. The cost of pelletizating will be higher than the mash feed because of the cost of pelletizing.…”
Section: Discussionsupporting
confidence: 93%
“…The study agreed with the findings of Laxmi et al 14 who reported no significant effect of sex on body weight of rabbits reared under different systems. The result of this study was also in line with the report of Sogunle et al 13 who stated that feed form and particle size had no significant effects on the parameters measured.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, the size of grain particles and feed composition during the initial growth stages can profoundly affect chicken growth performance. Further processing methods, such as pelleting and crumbing, also play a role in influencing growth (Sogunle et al, 2013).…”
Section: )mentioning
confidence: 99%
“…The birds fed pelletized feed performed better compared to those fed mash feed. According to Sogunle OM et al [29], the effect of the particle size of diets on broiler performance is confounded by the complexity of the diet and further processing methods. Pelleting is an expensive process, but its use is justified on the basis of the performance improvements.…”
Section: Feed Form Parameters On Broiler Performancementioning
confidence: 99%